Mechanical characteristics and damage evolution of granite under freeze–thaw cycles - Chen, Dun; Li, Guoyu; Li, Jinming; Du, Qingsong; Zhou, Yu; Mao, Yuncheng; Qi, Shunshun; Tang, Liyun; Jia, Hailiang; Peng, Wanlin (Frontiers in Energy Research, 2023)
Rocks in cold regions experience freeze–thaw (F–T) cycles, which have a significant impact on their mechanical properties, causing a series of engineering challenges that threaten engineering stability. To investigate the mechanical characteristics and damage evolution of granite under the influence of F–T cycles, the microstructural evolution and macroscopic mechanical properties of granite were analyzed by conducting P-wave velocity tests, computed tomography scanning, and uniaxial compression tests subjected to different F–T cycles. The results revealed the following: 1) the number of F–T cycles and saturated water content significantly impact on the mechanical properties of granite; 2) as the number of F–T cycles increases, the P-wave velocity, peak strength, elastic modulus, and coefficient of frost resistivity of granite gradually decrease, but the F–T damage values increase; 3) when the number of F–T cycles is less than 40 but within a certain range (0–100), the damage variable of granite increases rapidly, but then gradually tends to stabilize; 4) the damage gradually steadily spreads to the central region of the granite sample as the number of F–T cycles increases, and the ends and marginal regions of the granite samples are more susceptible to damage, and 5) three damage variables with different definitions (elastic modulus, density, and porosity) can be used to predict the degree of damage of granite under F–T cycles.